Indications, algorithms, and outcomes for coronary artery bypass surgery in patients with acute coronary syndromes. Issue 4 (June 2016) - Yerokun, Babatunde A.; Williams, Judson B.; Gaca, Jeffrey; Smith, Peter K.; Roe, Matthew T.
Abstract : For patients with a non-ST-segment elevation acute coronary syndrome (NSTE-ACS), guideline recommendations and treatment pathways focus on revascularization for definitive treatment if the patient is an appropriate candidate. Despite the widespread use of revascularization for NSTE-ACS, most patients undergo a percutaneous coronary intervention, whereas a minority of patients undergo coronary artery bypass grafting. Focusing specifically on the USA, the contemporary utilization, preoperative and perioperative considerations, and outcomes of NSTE-ACS patients undergoing coronary artery bypass grafting have not been comprehensively reviewed.